Study of an Antarctic Thermophilic Consortium and Its Influence on the Electrochemical Behavior of Aluminum Alloy 7075-T6 - Paez-Collio, M; Paez-Collio, M; Blamey-Alegria, J (Elsevier B.V., 2020)
Common alloys used for the manufacture of aircrafts are subject to different forms of environmental deterioration. A major one is corrosion, and there is a strong body of evidence suggesting that environmental microorganisms initiate and accelerate it. The development of an appropriate strategy to reduce this process depends on the knowledge concerning the factors involved in corrosion. In this work, a biofilm forming bacterial consortium was extracted in situ from the corrosion products formed in an aircraft exposed to Antarctic media. Two thermophilic bacteria, an Anoxybacillus and a Staphylococcus strain, were successfully isolated from this consortium. Two extracellular enzymes previously speculated to participate in corrosion, catalase and peroxidase, were detected in the extracellular fraction of the consortium. Additionally, we assessed the individual contribution of those thermophilic microorganisms on the corrosion process of 7075-T6 aluminum alloy, which is widely used in aeronautical industry, through electrochemical methods and surface analysis techniques. © 2019